The reality of using virtual classrooms in teaching English to the primary stage from the perspective of their teachers: A field study - Aljurijeer, Shamma Suliman (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to highlight the impact of using virtual classrooms in teaching English at the primary school level, focusing on the experiences of English language teachers in the Al-Qassim region, Unaizah. The study employed a descriptive-analytical method, gathering both quantitative and qualitative data through surveys and personal interviews, and analyzing this data using various statistical methods, The results revealed that virtual classrooms have several advantages that contribute to improving student interaction and academic achievement. Among these benefits are the ability to access educational materials anytime and anywhere, and the use of interactive tools that make the learning process more engaging for students. However, virtual classrooms also face certain technical and organizational challenges that can affect their effectiveness, such as internet connectivity issues and difficulties in time management. Based on the findings, several recommendations were made to enhance technical support, provide intensive training programs for teachers, develop interactive educational content, improve time management and organization of virtual classrooms, and strengthen interaction and communication between teachers, students, and parents. Additionally, regular evaluations should be conducted to improve and develop the virtual learning environment. This study emphasizes the importance of using virtual classrooms as an effective educational tool, especially in light of the challenges facing traditional education, such as health crises and geographical constraints. It underscores the necessity of providing the necessary support for teachers to ensure the effective use of this tool to achieve the desired educational objectives. In conclusion, we hope that this study will contribute to the improvement and development of virtual education at the primary school level in the Arab region and serve as an impetus for further research and studies in this field to ensure the provision of high-quality education for all students.